Fabrication of dual‐layer poly(styrene‐b‐4‐vinyl pyridine)–poly(vinylidene fluoride) membranes with tailored pore sizes under 10 nm via surface quaternization. Issue 9 (8th October 2018) - Su, Y.; Liu, Y.; Liu, T.; Wang, X.
ABSTRACT: Block copolymer membranes can be applied to precise size‐based separation because of their highly ordered surface morphology and adjustable pore sizes. However, there is a lower limit of the scale of block copolymer self‐assembly; this makes it a challenge to tailor the pore size down to below 10 nm. In this study, poly(styrene‐ b ‐4‐vinyl pyridine) membranes were modified to quaternized selective layers with pores smaller than 10 nm and were supported by poly(vinylidene fluoride) hollow fibers as the substrate to provide a high mechanical strength. Two reactants, methyl iodide and 2‐chloroacetamide, were used in the quaternization. With this one‐step chemical modification, the molecular weight cutoff was reduced from 190 to 8 kDa, and the surface pore sizes were narrowed down from 20–30 to 3 nm; this bridged the gap of tailored pore sizes down to below 10 nm. Such membranes are promising candidates for low‐molecular‐weight separation with high resolution. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47137. Abstract :